(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2024)
This article critically reviews the ideas presented by Jespersen on formal and notional differences in expressions. This review aims to explore the interplay between formal and notional variations in utterances, examining how these distinctions influence communication and interpretation. While formal consistency ensures clarity and adherence to linguistic rules, notional flexibility allows for adaptation to diverse contexts, intentions, and interpretations. The review highlights matches and mismatches between formal and notional categories not only from English but also from Nepali and Limbu languages. The review concludes that the form-notion relationship is either divergent, convergent or sometimes overlapping. Understanding these relationships enhances our grasp of language as a tool for both structured expression and nuanced meaning.